2018
DOI: 10.3389/fpls.2018.00256
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-Stimulated Triacylglycerol Breakdown and Energy Turnover under Salinity Stress Contributes to the Maintenance of Plasma Membrane H+–ATPase Activity and K+/Na+ Homeostasis in Sweet Potato

Abstract: Melatonin (MT) is a multifunctional molecule in animals and plants and is involved in defense against salinity stress in various plant species. In this study, MT pretreatment was simultaneously applied to the roots and leaves of sweet potato seedlings [Ipomoea batatas (L.) Lam.], which is an important food and industry crop worldwide, followed by treatment of 150 mM NaCl. The roles of MT in mediating K+/Na+ homeostasis and lipid metabolism in salinized sweet potato were investigated. Exogenous MT enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 59 publications
4
71
0
Order By: Relevance
“…The dynamic balance of ions in plant cells plays an important role in plant growth and development, which can protect enzyme activity, and maintains membrane potential and osmotic pressure, thus maintaining cell volumes. Previous studies have demonstrated the potential of exogenous melatonin application in mediating K + /Na + homeostasis and relative uptake rates of K + and Na + under salt stress in sweet potato [47]. Under salt stress, Na + and Clions rush into the cells of seeds, causing the accumulation of Na + , affecting the absorption of K + by plants, and causing ionic toxicity [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic balance of ions in plant cells plays an important role in plant growth and development, which can protect enzyme activity, and maintains membrane potential and osmotic pressure, thus maintaining cell volumes. Previous studies have demonstrated the potential of exogenous melatonin application in mediating K + /Na + homeostasis and relative uptake rates of K + and Na + under salt stress in sweet potato [47]. Under salt stress, Na + and Clions rush into the cells of seeds, causing the accumulation of Na + , affecting the absorption of K + by plants, and causing ionic toxicity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, melatonin could significantly reduce Na + accumulation and increase K + content in maize seeds under salt stress [34]. Yu et al [51] proposed a novel mechanism for melatonin-mediated salt tolerance, i.e., melatonin supplementation decreased the oxidative damage induced by salinity, perhaps by directly scavenging H 2 O 2 or enhancing the activities of antioxidative enzymes. In addition, melatonin might control the expression of ion-channel genes (MdNHX1 and MdAKT1) under salinity and maintain ion homeostasis and thus improve salinity resistance in plants exposed to exogenous melatonin [52].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is essential for normal growth and development, such as stomatal closure, the auxin signaling pathway, starch synthesis, plant regeneration, and root formation, as well as for defense against an array of biotic and abiotic stressors, including high light, pathogens, salt, senescence, and high temperature, among others . The functional roles of melatonin in plants are associated with crosstalk with plant hormones, such as auxin, cytokinin, salicylic acid, and abscisic acid …”
Section: Introductionmentioning
confidence: 99%
“…stressors, including high light, 13 pathogens, 14 salt, 15 senescence, 16,17 and high temperature, 18 among others. 19 The functional roles of melatonin in plants are associated with crosstalk with plant hormones, such as auxin, cytokinin, salicylic acid, and abscisic acid.…”
mentioning
confidence: 99%
“…In addition, exogenous melatonin can also prevent the accumulation of triacylglycerol and promote fatty acid β-oxidation and energy conversion under salt stress conditions. So it is helpful for improving PM H + -ATPase activity, activating gene expression of Na + -K + reverse transporter, and maintaining K + /Na + homeostasis of sweet potato (Solanum tuberosum L.) [67]. Application of 0.5 μmol L −1 exogenous melatonin can alleviate symptoms of green leaf loss, reduce the accumulation of Na + , improve phenols, ascorbic acid and glutathione etc., and promote the related activity of antioxidant enzymes, to alleviate the oxidative damage in salt-stressed tomato [68].…”
Section: Regulation Of Melatonin Resistance To Abiotic Stressmentioning
confidence: 99%